192k views
3 votes
H(y)=9/5 • 2y at y=-2

User Nilo Alan
by
5.0k points

1 Answer

4 votes

Answer:


H( - 2) = - 7 (1)/(5)

Explanation:

We want to evaluate the equation


H(y) = (9)/(5) * 2y

at y=-2

We just have to substitute to obtain;


H( - 2) = (9)/(5) * 2 * - 2

We now multiply to get:


H( - 2) = (9)/(5) * - 4

This is the same as:


H( - 2) = (9)/(5) * ( - 4)/(1)

We multiply the numerators separately and denominators separately to get:


H( - 2) = (9 * - 4)/(5 * 1)


H( - 2) = ( - 36)/(5)

This implies that


H( - 2) = - 7 (1)/(5)

User Paladini
by
5.0k points